2012
DOI: 10.3109/07388551.2012.732031
|View full text |Cite
|
Sign up to set email alerts
|

Human cytochrome b5 reductase: structure, function, and potential applications

Abstract: Cytochrome b5 reductase is a flavoprotein that is produced as two different isoforms that have different localizations. The amphipathic microsomal isoform, found in all cell types with the exception of erythrocytes, consists of one hydrophobic membrane-anchoring domain and a larger hydrophilic flavin catalytic domain. The soluble cytochrome b5 reductase isoform, found in human erythrocytes, is a truncated protein that is encoded by an alternative transcript and consists of the larger domain only. Cytochrome b5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 99 publications
0
67
0
1
Order By: Relevance
“…CYB5R3 (NADH-cytochrome b5 reductase 3) is a membrane-bound enzyme found in the plasma membrane, mitochondrial outer membrane, endoplasmic reticulum, and other membranes of most cell types, while a soluble form is present in red cells (30). CYB5R3 participates in cholesterol biosynthesis, fatty acid homeostasis, and P-450-mediated hydroxylation of drugs and steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYB5R3 (NADH-cytochrome b5 reductase 3) is a membrane-bound enzyme found in the plasma membrane, mitochondrial outer membrane, endoplasmic reticulum, and other membranes of most cell types, while a soluble form is present in red cells (30). CYB5R3 participates in cholesterol biosynthesis, fatty acid homeostasis, and P-450-mediated hydroxylation of drugs and steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…CYB5R3 participates in cholesterol biosynthesis, fatty acid homeostasis, and P-450-mediated hydroxylation of drugs and steroid hormones. Finally, CYB5R3 is involved in the trans-plasma membrane redox system that both protects against extracellular oxidants and prevents initiation of apoptosis by specific mechanisms (30,31). CYB5R3 is believed to play a role in cellular aging (31), and Siendones and colleagues (32) showed that CYB5R3 is involved in protection against cellular senescence as the primary human fibroblasts aged.…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has been made in uncovering the mechanisms of these anticancerous properties. The observed cellular effects include oxidative DNA damage (Elahian et al, 2012), the induction of mitochondria-mediated apoptosis, inhibition of phosphatases, and disruption of the pH gradient in various cellular compartments, and DNA intercalation, cell cycle arrest in late G1, and caspase activation Perez-Tomas et al, 2003;Francisco et al, 2007;Williamson et al, 2007).…”
mentioning
confidence: 99%
“…However, the use of iNO can lead to excessive oxidative stress and toxic levels of MetHb (methemoglobinemia) 7,8 . To prevent clinically significant methemoglobinemia, infants receiving iNO have MetHb levels checked frequently; however, some centers are questioning the utility of this practice 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…A soluble form of these proteins in the erythrocytes is responsible for reducing MetHb back into functional hemoglobin. Several studies have demonstrated that methemoglobinemia is associated with genetic variations in both CYB5A and CYB5R3 , resulting in decreased enzyme activity 7,1115 .…”
Section: Introductionmentioning
confidence: 99%